Economic valuation of ecotourism resources in yankari game reserve, Bauchi Nigeria - Adamu, Abdullahi; Yacob, Mohd Rusli; Radam, Alias; Hashim, Rohasliney; Usman, Adam Shehu (Elsevier, 2015)
Ecotourism is regarded as an ideal mechanism for achieving both economic and ecological sustainability. The objective of this study is to determine the tourists’ willingness to pay for conservation in Yankari game reserve using a dichotomous choice contingent valuation method (DC-CVM) on 335 local tourists. The result of the study showed that the mean willingness to pay as entrance fee by a tourist is 508 Naira (USD 3.4). The findings of this study would provide a guide to the management of the game reserve to take into account the benefits associated with resources conservation and the need to review their pricing policy.